Robustness in econometrics - Kreinovich, Vladik; Songsak Sriboonchitta; Huynh, Van-Nam (Studies in computational intelligence, 2017)
This book presents recent research on robustness in econometrics. Robust data processing techniques? i.e., techniques that yield results minimally affected by outliers? and their applications to real-life economic and financial situations are the main focus of this book. The book also discusses applications of more traditional statistical techniques to econometric problems. Econometrics is a branch of economics that uses mathematical (especially statistical) methods to analyze economic systems, to forecast economic and financial dynamics, and to develop strategies for achieving desirable economic performance. In day-by-day data, we often encounter outliers that do not reflect the long-term economic trends, e.g., unexpected and abrupt fluctuations. As such, it is important to develop robust data processing techniques that can accommodate these fluctuations.